DETERMINANTS OF EARLY MARRIAGE IN INDONESIA: A SYSTEMATIC REVIEW - Sri Windiarti; Besral Besral (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Early marriage is a formal or informal marriage that entered by individuals before the age of 18. In Indonesia, the marriage age is legally regulated in the Marriage Law with age limit of 16 years for female. This phenomenon contributed to the high number of early marriages and its impacts on maternal and child health. This study aims to examine the determinants of early marriage in Indonesia. Methods: Journal articles were collected by searching in academic article database, such as Scopus, Google Scholar, Pubmed from 2016 to 2018. Authors used the PRISMA-P protocol (Prefed Reporting Items for Systematic review and Meta-Analysis Protocols) in 2009 as systematic writing guidelines. Results: Determinants of early marriage in Indonesia were unwanted pregnancy, peer influence, parent role, education level, knowledge of reproductive health, family economic status, culture, and media exposure. Conclussions: Reviewing Indonesian marriage law is needed to reduce early marriage cases in Indonesia. Improving quality of reproductive health services, improving women's education and improving the economic status of the family is equally important to prevent early marriage and improve maternal and child Health in Indonesia.